Meromorphic continuation of certain distributions (2017)
"In the International Congress of Mathematicians of 1954, the mathematician I: M. Gelfand formulated a question concerning the analytic continuation of certain distributions. In 1972, J. Bernstein provided an affirmative answer to this question by proving the existence of the Bernstein-Sato polynomials. In this document, the existence of such polynomials is proved by following Bernstein-s article and, also, the meromorphic continuation of the distributions considered in Gelfand-s question is explicitly performed."--Tomado del Formato de Documento de Grado